Herpes simplex and herpes zona represent a danger of contagion to the medical profession, especially the dental profession. - Lucero F, Ricardo (Revista Universidad de Guayaquil, 1988)
The pathogenic agent of this condition is a VIRUS. This microorganism is made up of the most rudimentary organization; but with the capacity to reproduce; It is made up of DESO-XYRIBONUCLEIC ACID AND A PROTEIN ENCLOSURE. The virus that attacks man and causes Herpes Simplex is called ANDREWES' HERPES HOMINIS. This microorganism produces a latent infection and, if stimulated, the virulence causes the well-known "Calenturas" or Fires that almost always occur on the lips.